Managing projects financed by funding institutions - Telles, Maria Hortência da Costa; Costa, Stella Regina Reis da (Revista Gestão da Produção Operações e Sistemas, 2008)
Currently, one is aware about technological competence as a strategic key to the economic, social and political development of the industrial enterprises and countries where they are set. But it is clear the necessity of government support in financing of research and development projects on the defined areas of the technological and scientific policies. However, the big challenge faced by the institutions that do the scientific and technological research is to develop, introduce and improve a methodology and a management projects model financed by the government fomentation enterprises that fit the organizational environment and the culture of these institutions. In spite of the amount of literature avaiable about management projects and some well known models, none fit very well in the reality that interferes with these projects. This is the context that this work was proposed through a case study developed in the Scientific and Industrial Metrology Board (Dimci) at the National Institute of Metrology, Normalization and Industrial Quality (Inmetro). It was written after having a diagnosis made out of the data obtained from a survey. This survey was based on the activities envolving the projects in the institution, interviews with the coordinators of the projects, and other public research enterprise, similar to Inmetro. The diagnosis resulted in a proposal for a management model of the projects based on the standardization of the procedures and the controls necessary to provide the clearness of information about how the projects are being carried out. The aim is not only foster better results and the consequent improvement of the quality of population, but also to offer Brazilian products and services the opportunity to compete in the international market. Keywords: Projects management, projects management methodology, Research and technology development institution, projects office.